Restoration Potential of Sedge Meadows in Hand‐Cultivated Soybean Fields in Northeastern China. Issue 6 (11th April 2013) - Wang, Guodong; Middleton, Beth; Jiang, Ming
Abstract Sedge meadows can be difficult to restore from farmed fields if key structural dominants are missing from propagule banks. In hand‐cultivated soybean fields in northeastern China, we asked if tussock‐forming Carex and other wetland species were present as seed or asexual propagules. In the Sanjiang Plain, China, we compared the seed banks, vegetative propagules (below‐ground) and standing vegetation of natural and restored sedge meadows, and hand‐cultivated soybean fields in drained and flooded conditions. We found that important wetland species survived cultivation as seeds for some time (e.g. Calamogrostis angustifolia and Potamogeton crispus) and as field weeds (e.g. C. angustifolia and Phragmites australis). Key structural species were missing in these fields, for example, Carex meyeriana. We also observed that sedge meadows restored without planting or seeding lacked tussock‐forming sedges. The structure of the seed bank was related to experimental water regime, and field environments of tussock height, thatch depth, and presence of burning as based on Nonmetric Multidimensional Scaling analysis. To re‐establish the structure imposed by tussock sedges, specific technologies might be developed to encourage the development of tussocks in restored sedge meadows.